2021
DOI: 10.3390/genes12030384
|View full text |Cite
|
Sign up to set email alerts
|

iVar, an Interpretation-Oriented Tool to Manage the Update and Revision of Variant Annotation and Classification

Abstract: The rapid evolution of Next Generation Sequencing in clinical settings, and the resulting challenge of variant reinterpretation given the constantly updated information, require robust data management systems and organized approaches. In this paper, we present iVar: a freely available and highly customizable tool with a user-friendly web interface. It represents a platform for the unified management of variants identified by different sequencing technologies. iVar accepts variant call format (VCF) files and te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…In addition to the potential for recombination events, we also evaluated potential associations between identified mutations and the severity of disease in the patient. Studies suggested that missense mutations could be related to the virus’s ongoing adaptation, reduced symptoms, or disease severity, along with changes in other characteristics such as transmission rates [ 28 , 29 ]. Therefore, we examined the impacts of frequencies of silent and missense mutations on four groups of variants and patient outcomes: Omicron-ICU (group A), Omicron-not-ICU (group B), Delta-ICU (group C), and Delta-not-ICU (group D) ( Supplemental Figure S3 , Supplemental Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the potential for recombination events, we also evaluated potential associations between identified mutations and the severity of disease in the patient. Studies suggested that missense mutations could be related to the virus’s ongoing adaptation, reduced symptoms, or disease severity, along with changes in other characteristics such as transmission rates [ 28 , 29 ]. Therefore, we examined the impacts of frequencies of silent and missense mutations on four groups of variants and patient outcomes: Omicron-ICU (group A), Omicron-not-ICU (group B), Delta-ICU (group C), and Delta-not-ICU (group D) ( Supplemental Figure S3 , Supplemental Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Bwa-mem [ 27 ] was used for paired-end reads mapping to the Wuhan-Hu-1 reference genome (NCBI RefSeq accession NC_045512.2). Primer trimming was performed with iVar [ 28 ] using bed files specific to Artic V4.1 or Varskip2, respectively. Trimmed bam files were then realigned, deduplicated for final coverage evaluation, and called for variants using “ivar variants −q 20 −t 0.3 −m 30”.…”
Section: Methodsmentioning
confidence: 99%
“…Libraries were sequenced on the Illumina NextSeq1000 (2 × 109). Sequencing reads adapter sequences were trimmed using trim-galore, aligned to the Wuhan1 reference genome (MN908947.3) using the Burrows-Wheeler aligner, BWA-MEM version 0.7.17-r1188 [15], and had their primer sequences trimmed using iVAR version 1.3.1 [16]. Pangolin version 3.1.14 [17], with its pangolin-designation libraries up to date at the time of analysis, was used to assign lineage designations.…”
Section: Sars-cov-2 Genome Sequencing and Analysismentioning
confidence: 99%
“…Trimmed reads were mapped to a known reference rabies genome sequence using the Bowtie2 assembler version 2.3.4.3 (http://bowtie-bio.sourceforge.net/bowtie2). The consensus genome was called using iVar consensus version 1.2.3 (22). The complete coding genome sequences of the RRVs sequenced in this study have been deposited in the GenBank under Accession Numbers ON986428-30, ON986432-41, ON986443-55, ON986457, ON986467-69, ON986471-72, ON986474, ON986476-77, and ON986479-80.…”
Section: Genome Assemblymentioning
confidence: 99%